Netting the problem: a comprehensive analysis of marine litter on artisanal fishers - Guerrato, Nicole R.; Gonçalves, Leandra R. (Frontiers in Ocean Sustainability, 2025)
Marine litter, a critical global challenge, has gained prominence in international discourse, particularly during the United Nations Decade of Ocean Science for Sustainable Development. While extensive scientific literature on the distribution, origin, and ecological impacts of marine litter, research focusing on its socioeconomic impacts, especially on artisanal fishing communities, is markedly sparse. This study aims to address the gap in the impact of marine litter on small scale fishery through a systematic analysis of global research trends, patterns, and impacts of marine litter on fishing activities. Utilizing databases such as Scopus, SciELO, and repositories of theses and dissertations, the study analyzed scientific publications from 2011 to 2021, with keywords including “small-scale fishery,” “artisanal fishery,” “fisheries,” and “marine litter.” The analysis identified 14 articles that specifically address the impact of marine litter on the small-scale fisheries. These findings highlight a critical research gap: while the literature often portrays fishermen as sources of marine litter, notably through fishing gear, it seldom focuses on them as victims impacted by these environmental challenges. The study reveals the necessity for a more balanced research approach that integrates both environmental and social dimensions of marine litter, particularly in underrepresented regions. The increasing global focus on marine litter in recent academic research indicates a promising trajectory toward addressing these challenges comprehensively. This article underscores the urgency of broadening the scope of marine litter research to include the socioeconomic impacts on coastal communities, particularly artisanal fishermen. Such an approach is essential for developing effective, holistic solutions that address the intricate challenges posed by marine litter, balancing environmental protection with the livelihoods of coastal communities.